Pengaruh Website Fakultas Ilmu Sosial dan Hukum Universitas Negeri Jakarta terhadap Tingkat Pengetahuan Informasi Akademik: Survei Eksplanatif pada Mahasiswa Aktif Fakultas Ilmu Sosial dan Hukum Universitas Negeri Jakarta Angkatan 2024 - Wina Puspita Sari; Muria Putriana; Muhammad Ardi Himawan Nugroho; Adinia Sekar Rayani; Idzni Ramadhani Kamaludin; Inas Kurnia; Khairum Tri Anissa; Megan Restu Litani; Ruth Lydia Mutiara Sihombing (Pusat Riset dan Inovasi Nasional, 2025)
The rapid development of communication technology has made websites essential for providing accurate and accessible academic information. This study aims to determine the influence of the Faculty of Social Sciences and Law (FISH) website at Universitas Negeri Jakarta on students' academic information knowledge. Utilizing a quantitative approach and explanatory survey method, the study involved 92 students from the 2024 cohort selected through probability sampling with a simple random sampling technique. Data were collected via questionnaires and analyzed using statistical techniques. The findings indicate a strong relationship between website quality and academic information knowledge, with the dimension of information quality receiving the highest average score of 4.11. The correlation coefficient (r) was 0.754 with an R-squared value of 0.569, signifying that the website significantly contributes to students’ understanding of academic information. However, the interaction quality dimension received the lowest score, suggesting a need for better interactive features. These results underline the importance of improving website interactivity to enhance the overall student experience and academic support. The study concludes that a well-designed and informative website plays a crucial role in fulfilling students’ academic information needs.